Expression of cAMP and oxidative phosphorylation‐related lncRNAs in non‐functioning pituitary adenomas - Taheri, Mohammad; Nicknam, Amir; Bagan, Atena; Eslami, Solat; Rakhshan, Azadeh; Ghafouri‐Fard, Soudeh (Journal of cellular and molecular medicine, 2023)
Non‐functioning pituitary adenomas (NFPAs) are benign lesions in the pituitary gland with important morbidities. In this study, based on a bioinformatics analysis to identify the genes and pathways that display significant differences between tumour tissues of NFPA patients and normal pituitary tissues, we selected lncRNAs related to cAMP and oxidative phosphorylation pathways, namely DNAH17‐AS1, LINC00706 and SLC25A5‐AS1. Then, we aimed to investigate by means of RT‐qPCR, the expression of these lncRNAs along with two other lncRNAs, namely CADM3‐AS1 and MIR7‐3HG in NFPA samples compared to that in healthy tissues adjacent to the tumours. Transcripts of DNAH17‐AS1, LINC00706 and MIR7‐3HG were lower in NFPA samples compared with controls (Expression ratios (95% CI) = 0.43 (0.23–0.78), 0.58 (0.35–0.96) and 0.58 (0.35–0.96); p‐values = 0.009, 0.025 and 0.036, respectively). AUC values of ROC curves of DNAH17‐AS1, LINC00706 and MIR7‐3HG were 0.62, 0.61 and 0.62, respectively. Expression of CADM3‐AS1 was associated with the gender of patients in a way that it was lower in female patients (p‐value = 0.04). The level of SLC25A5‐AS1 was lower in subjects with disease duration lower than 1 year (p‐value = 0.048). We showed dysregulation of three lncRNAs in NFPA tissues and potentiates these lncRNAs as important regulators of pathogenic events in these tumours.